(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
While studies on the vulnerability to slum environments have received significant attention, albeit limited emphasis on its gender perspective. Put succinctly, recent evidence on the variations in the level of vulnerability especially for women and children in slum environments are lacking. To contribute to address this, this paper investigates the vulnerability of the population in the Douala IV slums of Cameroon, to environmental stressors. The characterization of environmental stressors in Douala reveals a complex interplay of challenges that impact the city’s urban environment. Key stressors include air and water pollution, deforestation, inadequate waste management, poor road network infrastructure, inadequate healthcare facility and services, inadequate social and economic infrastructure and services, and climate-related issues. These stressors are multifaceted, with implications for both human well-being and ecosystem health and the research Analyses variations in the level of vulnerability (exposure, sensitivity, adaptive capacity) to environmental stressors in Douala. A systematic sampling of 400 households was conducted in 8 neighborhoods in Douala. This was complemented by 15 key informant interviews and 15 focus group discussions Utilizing a double-layer sampling technique, the research focused on households in different neighborhoods, employing a systematic random sampling method. Questionnaires were administered, and the data were analyzed using SPSS Version 20 software. Results indicate that the women and childrenfaces moderate exposure to floods, with various frequencies reported. Additionally, the study reveals high exposure to other environmental stressors. Sensitivity to floods and water contamination is notable, with a significant portion of the population perceiving moderate to high sensitivity. Health vulnerability is exacerbated by challenges such as waste disposal in streams, standing water, and limited access to healthcare facilities. The findings underscore the interconnectedness of environmental factors and health vulnerability in slum environments. The study equally provides new insights on the relative vulnerability to environmental stressors from a gendered perspective